Clinical Outcomes and Effectiveness of Heart Transplantation in Patients With Systemic Light-chain Cardiac Amyloidosis. Issue 11 (16th June 2022) - Jeong, Hyehyun; Hwang, Inhwan; Kim, Jwa Hoon; Cho, Hyungwoo; Kim, Min-Seok; Lee, Sang Eun; Choi, Hyo-In; Jung, Sung-Ho; Lee, Jae Won; Yun, Tae-Jin; Park, Jeong-Jun; Kim, Miyoung; et al.
Abstract : Background: In systemic light-chain (AL) amyloidosis, cardiac involvement is a major determinant of survival; however, cardiac response is limited even after systemic treatment in a majority of patients, and some require heart transplantation. Additionally, limited information is available on specific indications for heart transplantation. We aimed to explore clinical outcomes of cardiac amyloidosis and its association with heart transplantation, including identifying factors favoring heart transplantation amenability. Methods: We retrospectively analyzed data from patients diagnosed with AL amyloidosis with cardiac involvement between January 2007 and December 2020 at a tertiary referral center. Results: Among 73 patients, 72 (99%) received systemic treatment, and 12 (16%) underwent heart transplantation. Characteristics at diagnosis were similar between heart transplant recipients and nonrecipients, although left ventricular ejection fraction tended to be lower in recipients (median 48% versus 57%, P = 0.085). Eight weeks after systemic treatment, 67% and 12% of patients achieved hematologic and brain natriuretic peptide responses. Overall survival was longer among heart transplantation recipients than nonrecipients, with 5-y survival rates of 61.1% (95% confidence interval, 25.5%-83.8%) versus 32.0% (95% confidence interval, 20.3%-44.4%; P = 0.022), respectively. Among the 34 with identifiable causes of death out of 51 deaths, 21 nonrecipients (62%) died of cardiac problems compared with none in the heart transplant recipients. Additionally, survival outcomes favored heart transplant recipients in most subgroups, including patients with higher Mayo 2004 European stage at diagnosis and with extracardiac involvement of amyloidosis. Conclusions: Heart transplantation can achieve long-term survival in appropriately selected patients with AL cardiac amyloidosis.